Cover Feature: N‐Heterocyclization in Gliotoxin Biosynthesis is Catalyzed by a Distinct Cytochrome P450 Monooxygenase (ChemBioChem 2/2021). (4th January 2021) - Scharf, Daniel H.; Chankhamjon, Pranatchareeya; Scherlach, Kirstin; Dworschak, Jan; Heinekamp, Thorsten; Roth, Martin; Brakhage, Axel A.; Hertweck, Christian
Abstract : The cover feature picture shows a pop‐art illustration of the pathogenic fungus Aspergillus fumigatus, which produces the infamous toxin, gliotoxin. Using targeted gene deletion, in silico studies and in vitro enzyme assays, we could elucidate a key late‐stage step in the biosynthesis of gliotoxin. A single cytochrome P450 monooxygenase, GliF, is capable of catalyzing a N‐heterocyclization reaction to form the hydroindole ring scaffold of gliotoxin. More information can be found in the communication by D. H. Scharf, C. Hertweck, et al.